Strengthening Economic Stability in Muslim Families: The Role of Islamic Financial Literacy Post-Covid-19 - Istianah, Istianah; Nugroho, Lucky (Social and Economic Bulletin, 2024)
The COVID-19 pandemic has significantly disrupted global economic stability, profoundly impacting Indonesia's Muslim households. As a population heavily reliant on informal sectors, declining incomes and limited access to necessities have created economic instability and challenges in applying Islamic financial principles, such as debt management, zakat, infaq, and sadaqah. This study examines the relationship between the pandemic and Muslim families' economic stability, investigates how Islamic financial literacy influences financial planning, and identifies challenges in implementing post-pandemic Sharia financial principles. This research systematically analyzes secondary data from scholarly articles, institutional reports, and Islamic legal sources using a literature review method. Findings reveal that the pandemic exacerbated economic hardships, limiting families' ability to fulfill Sharia obligations and forcing reliance on high-interest financing due to inadequate access to Islamic financial services. Islamic financial literacy emerged as a critical factor, empowering households to navigate economic challenges by fostering Sharia-compliant financial practices such as zakat allocation, usury avoidance, and halal investments. Challenges include low literacy levels, limited access to Islamic financial services, and difficulties fulfilling socio-religious obligations during economic crises. The study underscores the urgency of enhancing financial literacy and expanding access to Islamic financial products as vital measures to safeguard the economic stability of Muslim families. This research contributes to understanding Islamic financial planning's role during economic crises, highlighting the importance of integrating financial literacy and Sharia principles to support resilience. Novel insights include addressing structural barriers and proposing collaborative strategies for policymakers, Islamic financial institutions, and educators to ensure more inclusive and sustainable financial practices.